Entre Merleau-Ponty et Simondon: notes pour une approche écologique de la technologie numérique - Zoppis, Andrea (Scenari, 2021)
The proliferation of technological devices in our daily lives is moving faster and faster to the crisis of our relationality and our ability to understand the world. In this essay we try to focus on the need for a rethinking of technology starting from the phenomenology of the body of Merleau-Ponty and the philosophy of technique of Simondon. In the final part of the text, we will focus our attention on the relationship between corporeality and our experience of the screens, in an attempt to understand what are the dimensions through which it is possible to develop a reflection around the modulations and the re-articulations that sensibility and desire are undergoing. Rethinking technology from our embodied corporeality therefore becomes a crucial experience in trying to grasp the new mutations of our perceptual experiences.